Framing Assessment for Career Services: Telling Our Story. Issue 148 (December 2014) - Makela, Julia Panke; Rooney, Gail S.
Abstract : This chapter provides career professionals with an overview of current assessment practices and a framework for understanding how to bring practitioner‐led assessment activities into daily practice.